KANDUNGAN INFORMASI LABA BERSIH DAN ARUS KAS TERHADAP REAKSI PERUBAHAN RETURN SAHAM - Maharani, Satia Nur (Jurnal Keuangan dan Perbankan, 2012)
This paper presented an investigation of the listed LQ45 companies in Indonesia Security Exchange (BEI).This investigation examined the influence of earnings (EPS) and cash flows (OCF) to the in explaining stockreturns and stock price.This study used the accounting data of the companies listed in the BEI from 2008-2010.Furthermore, it employed a two of statistical procedures (regression analysis and path analysis). Also, 31Indonesian corporations were selected for testing the hypotheses. The results of this paper indicated the existenceof information value of earnings and there was sufficient evidence to confirm information content to makethe market react but cash flow does not have sufficient evidence to affect stock returns and stock price